Pengaruh Perbedaan Jenis Umpan pada Alat Tangkap Rawai Dasar terhadap Hasil Tangkapan Ikan di Perairan Bungus Padang Sumatera Barat - Nitra Rostia Meiza Putri; Sumaryam Sumaryam; Yusruddin Yusruddin (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2026)
Bungus waters, located in Padang City, are one of the important fisheries centers in western Indonesia with high diversity of demersal and pelagic fish species. Bottom longline is an environmentally friendly passive fishing gear widely used by fishers in these waters. This study aimed to determine the effect of different bait types used in bottom longline fishing gear on fish catch in Bungus waters. The method employed was experimental fishing using a Randomized Block Design (RBD), with three bait treatments, namely tuna, scad, and small squid, each replicated nine times. Catch data were analyzed using Analysis of Variance (ANOVA) followed by the Least Significant Difference (LSD) test. The results showed that differences in bait type had a highly significant effect on fish catch (F_calculated > F_table at the 1% level). Squid bait produced the highest catch with an average of 10.26 kg (41%), followed by scad at 8.1 kg (33%) and tuna at 6.52 kg (26%). The catch composition was dominated by grouper (44%), snapper (18%), threadfin bream (10%), and kurisi (9%). The use of squid bait was proven to be the most effective in increasing the productivity of bottom longline fishing gear in Bungus waters, Padang, West Sumatra.